Stock market contagion during the global financial crises: Evidence from the Chilean stock market - Sakthiharan Mahenthiran; Tom Gjerde; Berta Silva (International Journal of Financial Studies, 2020)
The study examines evidence for the transmission of the US and EU financial crises via investor holdings into the Chilean stock market following two global financial crises, in 2008 and 2011. The study modified the models of Bekaert et al. (2014), and Dungey and Gajurel (2015) on the 2007-2009 global financial crisis and extends the period to include the European debt crisis of 2010-2011. The study produced three main contributions. First, changes in the equity holdings of retail investors were a key source of contagion following the 2008 US financial crisis. Second, investor herding during the 2011 financial crisis is shown to be low based on the co-movement of equity holdings between the four investor groups studied. Third, investor behavior during the 2011 EU crisis differs from that of the 2008 US financial crisis, which we attribute to firms in Chile adopting international financial reporting standards (IFRS) and improving their corporate governance. We compared the findings to the prior contagion studies that rely on Chilean return data to highlight the contributions to international financial research, particularly as it relates to the functioning of emerging capital markets during financial crises.
Keywords: G11; G15; G40; 330; Chilean stock market; corporate governance; emerging capital markets; global financial crises; investor herding; investor holdings; stock market contagion